EFEKTIVITAS PENGGUNAAN KOAGULAN TAWAS DAN KAPUR DALAM MEREDUKSI SURFAKTAN DAN FOSFAT PADA LIMBAH LAUNDRY - Yusriani Sapta Dewi (FT-USNI, 2023)
The development of the clothes washing or laundry service industry continues to develop in residential areas increasing every year. This increases the amount of waste generated. So that it has a direct impact on the environment if it is not properly managed. Many contaminants are contained in laundry waste, including surfactants and phosphates which have the potential to have a damaging effect on aquatic ecosystems. In order to control pollution, waste water treatment is necessary. This study aims to eliminate the efficiency of the influence of variations in alum doses and variations in lime doses with the coagulation flocculation process in surfactant and phosphate levels only in washing waste.This study used coagulation and flocculation methods using 5% lime and 5% alum coagulants with alum doses of 5cc, 10cc, 15cc, 20cc and lime 2cc, 4cc, 6cc, 8cc. Fast stirring time of 1 minute at 100rpm, slow stirring 30 minutes at 20rpm with a settling time of 30 minutes. Based on the research analysis for the coagulation-flocculation treatment in laundry wastewater treatment using alum and lime coagulants is better at reducing the phosphate parameter having an efficiency value of 88.44% while the surfactant parameter has an efficiency value of 76.89%. Lime doses of 20cc alum and 8cc lime have a very significant effect on reducing surfactant and phosphate parameters below established quality standards and do not pollute the environment.